Pengaruh Inovasi dan Kualitas Produk terhadap Keputusan Pembelian Toyota Yaris - Vini Octaviani; Reminta Lumban Batu (UNIVED Press, 2022)
This study aims to explain the influence of innovation variables and product quality on purchasing decisions for Toyota Yaris. This study uses two independent variables, namely product innovation (X1), product quality (X2), and one dependent variable, namely the purchase decision (Y). The types of data used in this study are primary and secondary data. This research method uses quantitative methods with data collection techniques through distributing questionnaires to Toyota Yaris users. The sampling technique of this study was proportionate stratified random sampling using the slovin 10% formula. The sample used in this study amounted to 100 respondents. The instrument test was carried out using the validatas test and the reliability test. The data analysis method was carried out using descriptive statistical tests and hypothesis testing. The results showed that innovation had a significant influence on purchasing decisions for Toyota Yaris, and product quality had a significant effect on purchasing decisions for Toyota Yaris. The conclusion of this research is that innovation and product quality both have significant results on purchasing decisions.